LEARNING MOTIVATION AND ENGLISH ACHIEVEMENT OF ARABIC EDUCATION STUDENTS - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This study aims to analyze the relationship between learning motivation and English language learning achievement among students of the Arabic Language Education Study Program. This study uses a quantitative approach with a correlational research design. The sample of this study was 17 students of the Arabic Language Education Study Program. Data collection techniques were carried out using tests, interviews, and questionnaires. Data analysis used descriptive statistics and the Pearson Product Moment correlation test. The results showed that the total score of students' learning motivation reached 1,495, while the total score of English language learning achievement was 1,386. Thus, it can be concluded that increasing learning motivation has a positive relationship with English language learning achievement among students of the Arabic Education Department.